2012
DOI: 10.1007/s00339-012-7000-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced NO2 gas sensing properties of WO3 nanorods encapsulated with ZnO

Abstract: The influence of the encapsulation of WO 3 nanorods with ZnO on the NO 2 gas sensing properties was examined. WO 3 -core/ZnO-shell nanorods were fabricated by a two-step process comprising the catalyst-free thermal evaporation of a mixture of WO 3 and graphite powders in an oxidizing atmosphere and atomic layer deposition of ZnO. Multiple networked WO 3 -core/ZnO-shell nanorod sensors showed the response of 281 % at 5 ppm NO 2 at 300°C. This response value was approximately 9 times larger than that of bare WO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 37 publications
0
16
1
Order By: Relevance
“…Therefore, it is normal that the resistance of senor sharply dropped when the OM‐WO 3 /ZnO‐B sensor was exposed into reductive NH 3 gas. However, the resistance of senor declines when the sensor is placed in oxidizing NO x gas in this study, which is extremely different from the existing related reports …”
Section: Resultscontrasting
confidence: 72%
“…Therefore, it is normal that the resistance of senor sharply dropped when the OM‐WO 3 /ZnO‐B sensor was exposed into reductive NH 3 gas. However, the resistance of senor declines when the sensor is placed in oxidizing NO x gas in this study, which is extremely different from the existing related reports …”
Section: Resultscontrasting
confidence: 72%
“…WO 3 is believed to be a promising material applied as gas sensor. The investigations on its gas-sensing properties show that it has excellent sensitivity to toxic gas such as C 2 H 5 OH, NH 3 , NO 2 and H 2 S, especially low concentration [37][38][39]. However, the deep study of the influence of the exposure of certain facets on the sensing properties is still limited.…”
Section: Introductionmentioning
confidence: 98%
“…These oxygen molecules may be directly adsorbed on the surface of WO 3 nanorods by trapping free electrons from the conducting band, then transform into O 2 − and O − (Eqs. (1)- (3)) [34]. It has been confirmed that the number of adsorbed oxygen species will affect the gassensing properties of the sensor [35].…”
Section: No 2 -Sensing Mechanismmentioning
confidence: 79%